Draft Sixth Five year Plan (1980-85) and Annual Plan (1981-82) Volume VII - Planning Commission (Planning Commission, 1980)
It is proposed that the Departments of Physiology be upgraded and Neurophysiology respiratory unit and experimental and research Centre be set up in this year. The staff for the expansion of the Department and for setting up of these two units and the equipment required for these two units have therefore been proposed for provision of this Department. In order to carry on postgraduate teaching classes, research work and to bring the department to standard level
Government of Jammu and Kashmir
Planning and Development Department Srinagar
Keywords: General Education; Art and Culture; Technical Education; Provision of Schooling Facilities; Non-formal ''Education; High & Higher Secondary Schools; Adult Education; Universality of Elementary Education; Other Programmes; Research and Evaluation; Construction Programme